EFFECT OF DEGASSING AND GRAIN REFINEMENT ON HOT TEARING TENDENCY IN Al8Si3Cu ALLOY - Uludağ, Muhammet; Cetin, Remzi; Dispinar, Derya; Tiryakioglu, Murat (Springer International Publishing Ag, 2018)
The effect of melt quality on hot tearing susceptibility of Al8Si3Cu alloy was examined under six different conditions, by using a traditional T-shaped mold. Grain refinement was carried out by two different modifiers: AlTi5B1 and Al3B. For each test, samples were cast before and after degassing of melt. Therefore, a new hot tearing tendency index was developed by both bifilm calculations and porosity that occurred in the middle of T-zone of casting parts. Results indicated that hot tearing of cast aluminum alloys was a complex phenomenon, and bifilms play a major role, especially by compensating for shrinkage and consequently contributing to the inconsistencies in results.
Keywords: casting; aluminum alloys; grain refining; simulation; hot tearing